Revision of Jurassic Protobranch Bivalves from Gebel Maghara, northern Sinai, Egypt - Ayoub-Hannaa, Wagih S.; Fürsich, Franz; Abdelhady, Ahmed A. (Journal of Paleontology, 2023)
The Jurassic rocks of Gebel Maghara, northern Sinai, Egypt, contain a well-preserved and highly diverse macrobenthic fauna, dominated by bivalves. This fauna, particularly bivalves and gastropods, have received little attention in the last 100 years. In an attempt to provide a sound database on the marine bivalve diversity of Egypt during the Jurassic period, a first faunal group, the protobranch bivalves, is reviewed in detail. Sixteen taxa (three of them new), belonging to two orders, five families, and nine genera are systematically described and compared to closely related Jurassic taxa from various locations, particularly in Europe and India. New species are Nuculoma douvillei n. sp., N. sinaiensis n. sp., and Palaeoneilo aegyptiaca n. sp. In addition, Palaeonucula cuneiformis (J. de C. Sowerby), P. muensteri (Goldfuss), Dacryomya diana (d'Orbigny), D. lacryma (J. de. C. Sowerby), and Praesaccella juriana Cox are identified from Jurassic strata of Egypt for the first time. The younger records of the genus Palaeoneilo have not been accepted by some researchers, since almost all exhibit only limited features. The genus occurs with certainty in the Middle Jurassic (Bajocian-Bathonian) rocks of Egypt, based on well-preserved external and internal characters. Similarly, Dacryomya and Ryderia from Bathonian-Kimmeridgian rocks of Egypt are younger than previously recorded from other parts of the world. The identified genera have wide geographic ranges and have been reported from different faunal provinces, which suggests that latitudinal climate differences did not influence their distribution pattern to a great extent. UUID: https://zoobank.org/7f3a9185-d690-4563-bdc0-df1c8d42ec0d.
CRIS-Team Scopus Importer:2023-07-21